2004
DOI: 10.1152/ajpheart.01074.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of α2D-adrenoceptor and eNOS in aortas from early and later stages of diabetes in Goto-Kakizaki rats

Abstract: Kobayashi, Tsuneo, Takayuki Matsumoto, Kazuyuki Ooishi, and Katsuo Kamata. Differential expression of ␣2D-adrenoceptor and eNOS in aortas from early and later stages of diabetes in Goto-Kakizaki rats. Am J Physiol Heart Circ Physiol 287: H135-H143, 2004; 10.1152/ajpheart.01074.2003.-The aim of the present study was to compare vascular dysfunction between the early (12 wk old) and later (36 wk old) stages of spontaneous diabetes in GotoKakizaki (GK) rats. We also evaluated the aortic expression of the ␣2D-adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
48
3
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 51 publications
9
48
3
1
Order By: Relevance
“…We and others have demonstrated that both aortic endothelial dysfunction and hypertension are present in type II spontaneously diabetic (db/db) mice and in fructose-fed insulin-resistant mice Kamata et al, 2001). However, our recent observation that both endothelial function and NO production are impaired in aortic strips from spontaneously type II diabetic Goto-Kakizaki rats seemed to conflict with our finding that the expressions of the mRNA and protein for endothelial NO synthase (eNOS) were increased in such aortae (Kobayashi et al, 2004a). Since endothelium-dependent relaxation seems to be attenuated in blood vessels in at least some diabetic models when the disease is wellestablished, it is possible that time-dependent changes in endothelial function may occur (e.g., a two-phase influence of diabetes over endothelium-dependent relaxation).…”
Section: Endothelium-dependent Relaxation In Diabetic Modelscontrasting
confidence: 99%
See 1 more Smart Citation
“…We and others have demonstrated that both aortic endothelial dysfunction and hypertension are present in type II spontaneously diabetic (db/db) mice and in fructose-fed insulin-resistant mice Kamata et al, 2001). However, our recent observation that both endothelial function and NO production are impaired in aortic strips from spontaneously type II diabetic Goto-Kakizaki rats seemed to conflict with our finding that the expressions of the mRNA and protein for endothelial NO synthase (eNOS) were increased in such aortae (Kobayashi et al, 2004a). Since endothelium-dependent relaxation seems to be attenuated in blood vessels in at least some diabetic models when the disease is wellestablished, it is possible that time-dependent changes in endothelial function may occur (e.g., a two-phase influence of diabetes over endothelium-dependent relaxation).…”
Section: Endothelium-dependent Relaxation In Diabetic Modelscontrasting
confidence: 99%
“…Jiang et al (1999) found that both vascular insulin-induced phosphorylation and activation of the components of insulin signaling from the receptor level downstream to Akt were blunted in these obese insulin-resistant rats. Our recent observation that both endothelial function and NO production are impaired in aortic strips from spontaneously type II diabetic Goto-Kakizaki rats seemed to conflict with our finding that the expressions of the mRNA and protein for endothelial NO synthase (eNOS) were increased in such aortae (Kobayashi et al, 2004a). However, a possible explanation may be that in the intact cells, NO synthesis is regulated independently of changes in eNOS enzyme activity.…”
Section: Pi3-k/akt Pathway and Endothelial Dysfunction In Type II Diacontrasting
confidence: 67%
“…Hyperinsulinemia has been reported in OLETF rats in previous studies 7,8) . In the present analysis, metabolic correction with insulin notably reversed the enhanced endothelial function in the diabetic model rats, which may be due to the downregulation of endothelial nitric oxide synthase (eNOS)/heme oxygenase (HO)-1 9) . Insulin administration also resulted in intimal hyperplasia, particularly subendothelial thickening with the potential to impede the diffusion of nitric oxide into smooth muscle required to induce relaxation 10) .…”
Section: Ultrasound Assessments Of the Carotid Arterial Flow And Plaquementioning
confidence: 60%
“…[3][4][5][6] Our recent observation that endothelial function and nitric oxide (NO) production are impaired in aortic strips from spontaneously type 2 diabetic GotoKakizaki rats seemed to conflict with our finding that the expressions of the mRNA and protein for endothelial NO synthase (eNOS) were increased in such aortas. 7 However, a possible explanation may be that in the intact cells, NO synthesis is regulated independently of changes in eNOS enzyme activity.…”
mentioning
confidence: 99%